The Oil Spill Recovery Institute : past, present, and future directions (National Academies Press, 2003)
"As a result of the 1989 Exxon Valdez Oil Spill in Prince William Sound, Congress passed the Oil Pollution Act of 1990 (OPA 90), and within that legislation, the Oil Spill Recovery Institute (OSRI) was born. This report assesses the strength and weaknesses of this research program, with emphasis on whether the activities supported to date address the OSRI mission, whether the processes used are sound, and whether the research and technology development projects are of high quality"--Publisher